An alternative method in distinguishing cattle transferrin phenotypes - Quinteros, Indalecio Rodolfo (1968)
A modification of the method described by Kristjansson (1963) allows easier distinction of the components and position of every major cattle transferrin phenotype. The modification is based on increasing the percentage of starch (15%) and reducing the pH of the gel buffer to 6.8. In all the experiments, when a voltage of 350 was applied, a tray of ice was placed over the starch gel for the remainder of the electrophoresis. Different cattle transferrin phenotypes from our modified electrophoresis method are composed as follows: Type A, 4 bands; D1, 4 bands; D1D2, 4 bands; D2, 4 bands; E, 4 bands; AD1, 6 bands; AD2, 6 bands; AE, 8 bands and sometimes 9 bands; D1E, 6 bands and sometimes 7 bands; and D2E, 6 bands. The position of the fourth D band is distinctly different in D1 vs. D2 types.